Initial evidences of criterion validity for the results of a Figural reasoning test for the selection of Indigenous students for the University of Costa Rica and the Technological Institute of Costa Rica - Montero-Rojas, Eiliana (2013)
The partial outcomes of a research project that studies the possible utilization of some psychometric tests, different to the ones used nowadays for admission process at the University of Costa Rica and The Costa Rican Technological Institute, as part of an specific selection process for young indigenous with academic potential for university studies are presented. The outcomes obtained by senior students from three indigenous high schools on the Figural Reasoning Test (PRF) and on the mentioned admission tests, are compared. Evidences of correlation between PRF and each admission test were found, it indicates an acceptable level of association between the constructs measured by these tests. Besides, the paired samples t tests with no indigenous population whom applied the same tests on 2008, showed a significant difference on favor of the PRF against the other two tests. That is the first evidence that supports the criterion validity in the context of its application as a possible selection instrument that complements the admission process on this group of population.